2016
DOI: 10.1038/srep38450
|View full text |Cite|
|
Sign up to set email alerts
|

Adsorption of methylene blue on an agro-waste oiltea shell with and without fungal treatment

Abstract: A lignocellulosic waste oiltea shell (OTS) was evaluated as an inexpensive sorbent to remove methylene blue (MB) from aqueous solution. Fungal treatment of OTS increased the MB adsorption by modifying the physicochemical properties of OTS and simultaneously produced laccase as a beneficial co-product. Without fungal treatment, the maximum amount of adsorption (qm) of MB by OTS was 64.4 mg/g, whereas the treatment with fungus Pycnoporus sp. and Trametes versicolor increased qm up to 72.5 mg/g and 85.7 mg/g, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 36 publications
3
16
0
1
Order By: Relevance
“…Therefore, under optimized conditions (318 K adsorption temperature, 5 mg PAAM/PA/PDA hydrogel in 8 mL solution, 50 mg L −1 initial dye concentration, and suitable pH values (5.5 for NR, 4.5 for MB, 10.0 for MV and YMB)), the maximum adsorption capacities (584.58 mg g −1 for NR, 405.99 mg g −1 for MB, 625.97 mg g −1 for MV, and 350.67 mg g −1 for YMB) can be obtained respectively. The maximum adsorption capacities are comparable to or higher than those of literature reported (as shown in Table 1 ) 14 23 , 39 49 .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Therefore, under optimized conditions (318 K adsorption temperature, 5 mg PAAM/PA/PDA hydrogel in 8 mL solution, 50 mg L −1 initial dye concentration, and suitable pH values (5.5 for NR, 4.5 for MB, 10.0 for MV and YMB)), the maximum adsorption capacities (584.58 mg g −1 for NR, 405.99 mg g −1 for MB, 625.97 mg g −1 for MV, and 350.67 mg g −1 for YMB) can be obtained respectively. The maximum adsorption capacities are comparable to or higher than those of literature reported (as shown in Table 1 ) 14 23 , 39 49 .…”
Section: Resultssupporting
confidence: 81%
“…Various techniques have been employed for treatment of dye-containing wastewater, including catalytic degradation 1 , ion exchange 8 , membrane separation 9 , coagulation-flocculation 10 , precipitation 11 , photo degradation 12 , biological degradation 13 and adsorption 14 23 , etc . Among these methods, adsorption is considered to be one of the most effective methods for its simplicity, high efficiency, flexibility, and insensitivity to toxic substance 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Coefficients of determination (R 2 ) related to the Langmuir model applied to TT and MB biosorption data (R 2 = 0.965 for TT; R 2 = 0.990 for MB) were higher than those for the Freundlich model (R 2 = 0.955 for TT; R 2 = 0.938 for MB). In addition, the biosorption of methylene blue and thioflavin T by agricultural by-products from the hop (Humulus lupulus L.) [27] and methylene blue by water hyacinth biomass [31], agro-waste oil tea shell [13], Anethum graveolens biomass [32] and Tremella fuciformis biomass [33] was very well fitted by Langmuir model. Table 2.…”
Section: Sorption Equilibrium In Single and Binary Systemsmentioning
confidence: 88%
“…To date, diverse algae, macroalgae, plant biomasses, agricultural residues as well as other biomaterials have been explored as adsorbents for removal of acidic, basic and reactive dyes from aqueous solutions [9][10][11][12][13][14][15][16][17]. Authors have reported that the biosorption capacity is highly dependent on solution pH, biosorbent dosage, temperature and concentration of other solutes present in solution.…”
Section: Introductionmentioning
confidence: 99%
“…and Trametes versicolor modified Oiltea shells was found to be 64.4 mg/g, 72.5 mg/g and 85.7 mg/g which indicate improved surface area and pore size as well as alteration in chemical composition and physic-chemical properties upon fungal treatment of oil tea shells. The sorption data of both Oiltea shells as such and fungus modified Oiltea shells was best represented by Langmuir adsorption isotherm and pseudo second order kinetic model; also sorption process was spontaneous and favorable [24]. Activated carbon prepared from coconut husk by sulphuric acid activation was assessed for removal of textile dyes Maxilon blue GRL and direct yellow DY 12.…”
Section: A Dye Removal Using Low Cost Bioadsorbents Derived From Agrmentioning
confidence: 99%